2022
DOI: 10.1007/s00384-022-04210-x
|View full text |Cite
|
Sign up to set email alerts
|

Computer-aided diagnosis of serrated colorectal lesions using non-magnified white-light endoscopic images

Abstract: Purpose: Computer-aided diagnosis systems for polyp characterization are commercially available but cannot recognize subtypes of sessile lesions. This study aimed to develop a computer-aided diagnosis system to characterize polyps using non-magni ed white-light endoscopic images.Methods: A total of 2249 non-magni ed white-light images from 1030 lesions including 534 tubular adenomas, 225 sessile serrated adenoma/polyps and 271 hyperplastic polyps in the proximal colon were consecutively extracted from an image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…It is worth noting that our method allows the endoscopist to build/use the model with a limited sample size using white light images from ordinary endoscopy, not NBI or magnified images. Our AI model with only white-light images outperform the SSA and TA classification model build in Nemoto et al [ 10 ], which obtain accuracy ranges from 77 to 87%. This might be due to the fact we combine the data argumentation with deep-learning model.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…It is worth noting that our method allows the endoscopist to build/use the model with a limited sample size using white light images from ordinary endoscopy, not NBI or magnified images. Our AI model with only white-light images outperform the SSA and TA classification model build in Nemoto et al [ 10 ], which obtain accuracy ranges from 77 to 87%. This might be due to the fact we combine the data argumentation with deep-learning model.…”
Section: Discussionmentioning
confidence: 82%
“…Therefore, using enhanced images to build an AI classification model can significantly limit the generality of the model. Nemoto et al [ 10 ] built an AI model that can distinguish SSA and TA using white-light images. Their accuracy ranges from 77 to 87%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study showed the difficulty of developing a CADx system able to distinguish SSLs from hyperplastic polyps. Nemoto et al 33 reported that their developed CADx showed a smaller area under the receiver operating characteristic curve (CADx vs. expert: 55% vs. 68-79%). This complication may be caused by interobserver variability among pathologists.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we initially selected 8 parameters that may affect the performance of DSA images (14,15): (1) the speed of contrast agent injection, (2) the timing of contrast agent injection, (3) the dose of x-ray, (4) the DSA imaging frame rate, (5) the pressure of contrast agent injection, (6) the flow velocity, 6) flow rate, (7) number of broken fibers (the number of cutting fibers of the dialyzer to simulate bleeding) and ( 8) the distance of contrast agent injection from the injection point to the dialyzer. In order to obtain a sufficient number of experiments, we used an orthogonal experimental design to create 27 experimental groups (Supplementary Material S2).…”
Section: Orthogonal Experimental Design For Dsa Imaging Parameter Opt...mentioning
confidence: 99%